Fault Detection with Crosshole and Reflection Geo-Radar for Underground Mine Safety - Jakob Kulich; Florian Bleibinhaus (Geosciences, 2020)
Ground-penetrating radar and crosshole radar are applied in an underground marble mine for fault detection and to test if different geological bodies can be distinguished. Boreholes are often drilled in advance of mining to clarify the locations of ore bodies and gangues. Here, such boreholes were used for crosshole investigations to supplement optical borehole imaging. Four boreholes were drilled along a profile with increasing offsets from 5 to 25 m. The crosshole measurements were performed with 100 MHz antennas. Tomographic panels were created up to a depth of 28 m and were complemented by reflection mode ground-penetrating radar (GPR) measurements along a 25 m-long profile with 100 and 250 MHz antennas. The GPR imaging successfully delineates the fault and karstification zones with higher water content due to their strong dielectric permittivity contrast compared to the surrounding geology.